Reducing stereotyped behavior: a component analysis of the DRI schedule - Jones, R S (British journal of clinical psychology, 1989)
Three people with mental handicaps took part in a study which investigated the effects of various components of the DRI schedule on their levels of stereotyped behaviour. Three single-case experiments were carried out each investigating a separate component. Results suggested that the reductive effects of DRI could not be attributed to either the density of reinforcement available or to the prompting component. The success of the schedule was primarily attributable to the non-contingent interaction between the subject and the experimenter.